2011
DOI: 10.1002/etc.602
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of acetochlor, S‐metolachlor, and atrazine in surface and subsurface soil horizons of Argentina

Abstract: Understanding herbicide sorption within soil profiles is the first step to predicting their behavior and leaching potential. Laboratory studies were conducted to determine the influence of surface and subsurface soil properties on acetochlor, atrazine, and S-metolachlor sorption. Soil samples were taken from horizons A, B, and C of two loamy soils of the humid pampas of Argentina under no-till management; horizon A was divided into two layers, A(0) (0-5 cm) and A(1) (5 cm to the full thickness of an A horizon)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 40 publications
(68 reference statements)
2
31
0
2
Order By: Relevance
“…In support of this assumption, previous studies have found strong sorption of S-metolachlor to surface soils, where the organic matter content is typically higher than at greater depth (e.g. Bedmar et al, 2011;Rice et al, 2002;Si et al, 2009). Subsequently, infiltration of precipitation leads to pesticide desorption and input into the dissolved phase of the source zone reservoir.…”
Section: Pesticide Model: Mass Transfer and Transportmentioning
confidence: 69%
“…In support of this assumption, previous studies have found strong sorption of S-metolachlor to surface soils, where the organic matter content is typically higher than at greater depth (e.g. Bedmar et al, 2011;Rice et al, 2002;Si et al, 2009). Subsequently, infiltration of precipitation leads to pesticide desorption and input into the dissolved phase of the source zone reservoir.…”
Section: Pesticide Model: Mass Transfer and Transportmentioning
confidence: 69%
“…The metolachlor adsorption in soil is quite high (Bedmar et al 2011) and increases with soil organic carbon content. The selectivity of metolachlor in sunflower is relatively good and, therefore, may also be used for early post-emergent application (Pannacci et al 2007), but spectrum of controlled weed is relatively narrow.…”
mentioning
confidence: 99%
“…Statistical analyses (Table 3) showed that the sorption of acetochlor in soils was highly correlated with soil organic carbon content (R = 0.99, P < 0.001), and the humic acid and fulvic acid carbon contents (R = 0.98 and R = 0.97, P < 0.001). Several studies have suggested that soil organic matter exhibits a high affinity for acetochlor and plays the most prominent role as a sorbent of acetochlor in soils (Wang et al 1999;Hiller et al 2008;Bedmar et al 2011). The calculated K oc values for acetochlor were similar among the soils, confirming that organic matter of the soils had similar sorption affinity for the herbicide and that TOC was the most important factor for acetochlor sorption in soils.…”
Section: Resultsmentioning
confidence: 65%
“…The different shapes of sorption isotherms might be attributed to the occurrence of more sorption mechanisms included in the acetochlor sorption, likely due to differences in composition of the soils and their heterogeneous nature. Several authors have reported non-linear isotherms of L-and S-types for acetochlor sorption in soils with contrasting physico-chemical properties (Taylor et al 2004;Hiller et al 2008;Bedmar et al 2011). Based on the K fs values, the extent of acetochlor sorption decreased with increasing soil depth for each soil type (Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation